Akhtar Raza Salimi's Novel "Jinder" Features Gandhara Culture - Ahmed, Aftab; Bibi, Rizwana; Khan, Muhammad Rizwan (sourcecoder, 2024)
The novel "Jinder" is a story from eternity, which began on the day when Hazrat Adam (peace be upon him) chewed the first grain of wheat. This story began as soon as man stepped on the earth and will continue until the trumpet is blown on the Day of Judgment. By eating the first grain of wheat, man had given his existence two grains of millet, and had torn his soul to the wire and the flesh on his body to the fiber. This story started running from the dark paths to the towers of light at the same time when Hazrat Insan first threw a few grains on a stone and hit another stone to fill the hell of his stomach. Of course, he would not have been able to strike the first blow well. The grains that were scattered by his wrong injury were scattered in such a way that even today man is still searching for these grains.